CLINICAL COURSE CHARACTERISTICS AND THERAPEUTIC APPROACHES OF COXARTHROSIS. - Kamolova Go’zaloy Odiljon qizi, (TADQIQOTLAR, 2025)
Abstract. Coxarthrosis, commonly referred to as hip osteoarthritis, has been recognized as a progressive joint disorder that predominantly affects older adults. Over time, the deterioration of cartilage and surrounding structures has led to pain, stiffness, and significant limitations in daily activities. This condition, though gradual in onset, has been shown to exert a heavy burden on individuals’ quality of life. In this paper, its clinical characteristics, diagnostic process, and treatment strategies are reviewed through an evidence-based lens. Conservative and surgical options have been outlined, with  recent  developments  and  patient-centered  approaches  considered  essential  for optimal care.